Modelling parameters characterizing selected water supply systems in lower Silesia province = Modelowanie parametrów wybranych systemów zaopatrzenia w wodę w województwie dolnośląskim - Nowogoński, Ireneusz; Ogiołda, Ewa (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The work presents issues of modelling water supply systems in the context of basic parameters characterizing their operation. In addition to typical parameters, such as water pressure and flow rate, assessing the age of the water is important, as a parameter of assessing the quality of the distributed medium.
Keywords: water supply system; water pressure; flow rate; water age; EPANET program; system zaopatrzenia w wodę; ciśnienie wody; prędkość przepływu; wiek wody; program EPANET